Comparison of Sensitivity to Glyphosate of Euphorbia davidii Populations = Comparação da Sensibilidade ao Glyphosate de Populações de Euphorbia davidii - Núñez Fré, F.R.; Juan, V.F.; Yanniccari, Marcos Ezequiel; Saint André, H.M.; Fernández, R.R. (2018)
Euphorbia davidii (Euphorbiaceae) is a summer annual weed present in the Province of Buenos Aires, Argentina. The aim of this study was to compare the sensitivity to glyphosate of different populations of Euphorbia davidii. Two techniques were used: a seed bioassay and shikimate determination in glyphosate-treated plants. Germination rates of seeds belonging to the populations from Espartillar, Barrow, Olavarria and Azul exposed to different concentrations of glyphosate were compared. Plants from the same locations treated with glyphosate were evaluated to determine shikimate levels. The most sensitive population was from Espartillar, with a CE50 (average effective concentration) of 4.00 g e.a. L-1. Based on this finding, the resistance index for each population was 1.76, 2.39 and 2.48 for Azul, Olavarria and Barrow respectively. Regarding glyphosate-treated plants in which shikimate levels were determined, a significant increase in the concentration of this metabolite was only observed in the population from Espartillar. Accumulation of shikimate was not detected in the other groups. These results show differential sensitivity to glyphosate of the evaluated populations.